Psychological flexibility and self-compassion in gay and heterosexual men: how they relate to childhood memories, shame and depressive symptoms - Matos, Marcela (2018)
This study explores differences between gay men (N = 53) and heterosexual men (N = 52) regarding memories of shame events and of warmth and safeness experiences with parents during childhood and adolescence, self-compassion, psychological flexibility, internal shame and depression. Also, it aims to explore whether psychological flexibility and self compassion play a role in the association between these memories and internal shame and depressive symptoms. Results confirmed the mediating role of psychological flexibility and self-compassion. These findings suggest the appropriateness of promoting acceptance and self-compassion towards difficult memories in a therapeutic setting with gay men experiencing shame and depressive symptoms.